“SCHOOLS FOR LADIES AND GENTLEMEN” AS A SPECIFIC FORM OF NON-FORMAL EDUCATIONAL INSTITUTIONS IN FAR EAST COUNTRIES (China, Japan, South Korea and Singapore) - Kalashnyk, Lyubov; Ruda, Nataliia; Oserska, Oksana; Nazarenko, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
”Schools for Ladies and Gentlemen" is a term commonly used to determine a non-formal educational institution in some of Far East countries where the students are taught mainly abroad ethics and aesthetics. Such educational institutions can be considered a vestige of the foreign countries` presence on the territory of the countries under consideration in the 19th-20th century, since it was the social activity of some European countries and US that largely determined the shape and value orientation of the education system in China, Japan, South Korea and Singapore in particular. The second half of the 20th century in the countries considered is characterized by a revision of foreign educational trends, which led to the departure of the abroad educational experience from the mass formal education. However, the social prestige of “foreign education” and the introduction of a child to “foreign ethical and aesthetic canons” as an indicator of financial well-being and social elitism has been preserved and has found its expression in the sphere of non-formal education in the form of clubs, circles, the services of private tutors, etc. The article examines the exact forms in which this trend is present in the educational sphere of one or another country in the Far East.